2016
DOI: 10.3389/fnagi.2016.00043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Detraining in Tendon Mechanobiology

Abstract: Introduction: Several conditions such as training, aging, estrogen deficiency and drugs could affect the biological and anatomo-physiological characteristics of the tendon. Additionally, recent preclinical and clinical studies examined the effect of detraining on tendon, showing alterations in its structure and morphology and in tenocyte mechanobiology. However, few data evaluated the importance that cessation of training might have on tendon. Basically, we do not fully understand how tendons react to a phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 58 publications
0
28
0
2
Order By: Relevance
“…In our study, participants were asked to finish the workout at hand in the shortest amount of time possible, leading to a much higher velocity in all repetitions, and probably less attention to technique. (Frizziero et al, 2016) also found that physical activity such as training after an injury, or other sudden detraining scenarios, should be performed cautiously and by following targeted rehabilitation programs to get the desirable effect on the affected tendon.…”
Section: Tendinopathy or Physiological Response?mentioning
confidence: 99%
“…In our study, participants were asked to finish the workout at hand in the shortest amount of time possible, leading to a much higher velocity in all repetitions, and probably less attention to technique. (Frizziero et al, 2016) also found that physical activity such as training after an injury, or other sudden detraining scenarios, should be performed cautiously and by following targeted rehabilitation programs to get the desirable effect on the affected tendon.…”
Section: Tendinopathy or Physiological Response?mentioning
confidence: 99%
“…This adaptation consisted of weight lifting sessions (50% body weight load), once a day, five days per week, in water at 30 ± 2 ‱ C. The training was induced by the instinctive reactions of rats submitted to a jump exercise protocol in a plastic tube (25 cm diameter and 40 cm length) with water at 30 ± 2 ‱ C. The overload was attached to the animal's chest by means of a vest fitted to its body. The numbers of sets [2][3][4] and repetitions [5][6][7][8][9][10] were adjusted daily and increased gradually. All sessions were performed in the afternoon after 4 p.m. Vertical jump protocol: After the adaptation week, the animals were submitted to the experimental jump protocol, which consisted in the first training week of: 4 sets of 10 jumps with a 30 s rest period between sets and overload of 50% of body weight.…”
Section: Training Protocolmentioning
confidence: 99%
“…It is generally presumed that the increased secretion of these growth factors and enzymes is responsible for the development of exercise-induced adaptations, which include an increased tendon cross-sectional area, tendon stiffness, and collagen crosslinking [2,8,9]. Thus, it is clear that physiological loads influence tendon cells, producing cellular signals that lead to positive adaptations to the tissue.On the other hand, a systematic review investigated the effects of training interruption on tendon mechanobiology, indicating that detraining (four weeks of no exercise in animals) causes rearrangement in the collagen fiber, increasing collagen type III and reducing collagen type I, causing a loss of resistance to tension, increasing rigidity and the risk of rupture in the entheses [10]. In addition, detraining leads to a reduction in collagen type I and III synthesis and tenocyte activity, despite the matrix metalloproteinases (MMPs) synthesized during the training phase remaining active, assisting tissue remodeling [10,11].Moreover, in sports, particularly in competitive athletes, the use of anabolic-androgenic steroids (AAS) has already become a chronic practice due to the continuous search for better performance [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even mechanical overloading is considered as the main risk factor, other intrinsic and extrinsic factors may contribute to the pathogenesis 2,3 . In particular, poor vascularity, underload, age, gender, as well as genetic, endocrine and metabolic factors may play a central role [4][5][6] . Over the last decade, various models have been proposed to explain the intrinsic pathogenic mechanism of tendinopathies, which determine the failed healing response.…”
Section: Introductionmentioning
confidence: 99%